(untitled) (INTERNATIONAL JOURNAL OF RECENTLY SCIENTIFIC RESEARCHER’S THEORY, 2025)
This article explores contemporary methods used in language learning to enhance learners’ proficiency, motivation, and communication skills. Emphasis is placed on communicative, task-based, and technology-integrated approaches, as well as learner-centered instruction. The effectiveness of these methods is examined through recent pedagogical research and classroom applications. The study concludes that a combination of innovative strategies yields higher learner engagement and improved outcomes in language acquisition.